Pusher Propeller Non-Harmonic Actuation For Active Vibration Control - Malarkey, H. F.; Smith, E. C.; Schmitz, S. U.; Zhang, J.; Floros, M. W. (My University, 2025)
The vibration control authority for coaxial rotor higher harmonic control (HHC) and a new pusher propeller active vibration control (AVC) system was evaluated with the Rotorcraft Comprehensive Analysis System (RCAS) coupled with the Viscous Vortex Particle Method (VVPM). Model refinements were implemented, and cockpit vibration predictions were validated against available flight test data, despite inconsistencies in the literature. A closed-loop HHC study for the XH-59A coaxial rotor predicted a maximum HHC pitch requirement of 2.3°. The theoretical basis for the pusher propeller AVC system was established by modulating steady pusher propeller hub loads at harmonics of the main coaxial rotor, even though the propeller rotates at a non-harmonic speed. A pusher propeller appended to the XH-59A model demonstrated the concept's feasibility in four stages.